Adolescents' perceptions and experiences of pregnancy in refugee and migrant communities on the Thailand-Myanmar border: a qualitative study - Carine Asnong; Gracia Fellmeth; Emma Plugge; Nan San Wai; Mupawjay Pimanpanarak; Moo Kho Paw; Prakaykaew Charunwatthana; François Nosten; Rose McGready (BMC, 2018)
Abstract Background Adolescent pregnancy remains a global health concern, contributing to 11% of all births worldwide and 23% of the overall burden of disease in girls aged 15-19 years. Premature motherhood can create a negative cycle of adverse health, economic and social outcomes for young women, their babies and families. Refugee and migrant adolescent girls might be particularly at risk due to poverty, poor education and health infrastructure, early marriage, limited access to contraception and traditional beliefs. This study aims to explore adolescents' perceptions and experiences of pregnancy in refugee and migrant communities on the Thailand-Myanmar border. Methods In June 2016 qualitative data were collected in one refugee camp and one migrant clinic along the Thailand-Myanmar border by conducting 20 individual interviews with pregnant refugee and migrant adolescents and 4 focus group discussions with husbands, adolescent boys and non-pregnant girls and antenatal clinic staff. Inductive thematic analysis was used to identify codes and themes emerging from the data. Results Study participants perceived adolescent pregnancy as a premature life event that could jeopardise their future. Important themes were premarital sex, forced marriage, lack of contraception, school dropout, fear of childbirth, financial insecurity, support structures and domestic violence. Supportive relationships with mothers, husbands and friends could turn this largely negative experience into a more positive one. The main underlying reasons for adolescent pregnancy were associated with traditional views and stigma on sexual and reproductive health issues, resulting in a knowledge gap on contraception and life skills necessary to negotiate sexual and reproductive choices, in particular for unmarried adolescents. Conclusions Adolescents perceive pregnancy as a challenging life event that can be addressed by developing comprehensive adolescent-friendly sexual and reproductive health services and education in refugee and migrant communities on the Thailand-Myanmar border. Creating a more tolerant and less stigmatising environment in these communities and their governing bodies will help to achieve this goal.